The role of the sports media in spreading health awareness to reduce sports injuries from the point of view of the players of the Palestinian and Yemeni football teams - Motaz Mohammad Saadi Al-Qaoud; Lamyaa Hassan Mohammad; Muhammad Hussein Al-Nadhari; Ghazwan Abdullateef Hassan (دراسات وبحوث التربية الرياضية)
The study aimed to identify the role of sports media in spreading health awareness to reduce sports injuries from the point of view of the players of the Palestinian and Yemeni football teams. The researchers used the descriptive analytical approach in a comprehensive survey method, where the study population consisted of players from the Yemeni and Palestine national teams, numbering (52) players. (26) players for each team. The questionnaire was used as a tool to collect data after verifying its validity and reliability. The study concluded that the sports media in Palestine and Yemen do not participate effectively in spreading health awareness to reduce sports injuries, especially television sports programs, and newspapers usually It addresses player injuries without delving into their causes and how to avoid them. In light of the results of the study, the researchers recommended several recommendations, the most important of which is that the sports media in Palestine and Yemen attach great importance to health awareness of sports injuries, because of their risks to players and the team.